THE USE OF SORAFENIB (NEXAVAR) IN TREATMENT OF PATIENT WITH DISSEMINATED PARATHYROID CANCER: A CASE REPORT - V. A. Gorbunova; E. A. Pigarova; L. Ya. Rozhinskaya; I. A. Voronkova; Yu. A. Krupinova; G. S. Emel’yanova; L. S. Kruglova; S. V. Shiryaev; M. B. Dolgushin; M. E. Bilik; E. A. Kobyakova; D. V. Komov (Опухоли головы и шеи, 2017)
Parathyroid carcinoma (PC) is a rare neoplasm with a prevalence of only 0.005 % of all malignancies, and less than 1 % among patients with primary hyperparathyroidism. The diagnosis can be challenging due to the rarity of the disease, similarity of clinical features to parathyroid adenoma, and lack of reliable morphological signs of the tumor. For metastatic cancer of the parathyroid gland does not exist standard drug therapy due to the rare occurrence of this disease. Chemotherapy and radiotherapy failed to show any significant effect on the course of the disease. We report the case of a 27-year old woman with PC previously misdiagnosed as benign thyroid nodule and multiple lung metastases. After the immunohistochemical study and confirm of diagnosis PC the patient was treatment with multikinase inhibitor sorafenib successfully.